PTH-074 The Presence of Total Anti-Drug Antibodies to Biologic Drugs Does not Adversely Affect Long-Term Outcomes in Crohn's Disease Patients with Adequate Drugs Levels and Absent Free Anti-Drug Antibodies. (17th August 2016) - Samaan, MA; Unsworth, N; Ward, M; Warner, B; Sanderson, JD; Arkir, Z; Irving, PM
Abstract : Introduction: The use of therapeutic drug monitoring (TDM) for anti-TNF drugs has become increasingly widespread over recent years. It is now used in many centres to guide clinical decisions regarding dose optimisation, the use of concomitant immunomodulators as well as switching or withdrawal of treatment. 1 TDM usually includes the measurement of serum trough levels of infliximab (IFX) or adalimumab (ADA) as well as anti-drug antibodies (ADAb). There are two different approaches to measuring ADAb; some techniques measure total ADAb (drug-ADAb complexes as well as free ADAb), whilst other measure only free ADAb. However, the clinical relevance of the differing data generated by these techniques is not yet fully understood. Methods: A prospective evaluation of trough drug levels and ADAb was performed using our standard ELISA assay (LISA TRACKER, Theradiag) in 145 IBD patients on anti-TNF agents between January and May 2014. This technique measures only free ADAb. The samples were also anaylsed using an ELISA assay that measures total ADAb (IDKmonitor, Immundiagnostik). Long term outcomes were evaluated for 21 (17 IFX, 4 ADA) patients with Crohn's disease (CD) who were found to have negative free ADAb but positive total ADAb. Outcome assessments were made by review of a prospectively maintained database, with a mean follow-up period of 22 months. Clinical outcome measures included; the need to escalate/switch/withdraw biologic treatment, infusion/injection-site reactions, documented clinical flare (HBI > 5) and need for steroid treatment. Biochemical outcome measures included; CRP > 5 mg/L and faecal calprotectin >150 ug/g. The subsequent development of positive free ADAb and subtherapeutic/undetectable drug levels were also collected as outcome measures. Results: Anti-drug antibody (ADAb) detection: Of the 21 CD patients with positive total ADAb and negative free ADAb at the time of initial sampling, 3 (14%) went on to subsequently develop positive free ADAb during the follow-up period. Sixteen patients (75%) were taking concomitant immunomodulators, including all 3 patients who subsequently developed free ADAb. The mean IFX trough level in patients who went on to develop free ADAb was 1.05 ug/ml, compared to 4.04 ug/ml in those who did not. Outcomes: All 3 (100%) of the patients who developed positive free ADAb subsequently went on to have subtherapeutic or undetectable drug levels and required a switch in anti-TNF therapy. Two of the 3 (67%) had a flare in disease activity with an elevated faecal calprotectin. Two (67%) also developed significant infusion reactions. Of the remaining 18 patients who did not subsequently developed free ADAb, only one patient (6%) required a switch in anti-TNF, 4 (22%) developed clinical flares and 3 (17%) required steroid treatment. None of the 18 patients who remained free ADAb negative had undetectable drug levels during the follow-up period. Conclusion: Long-term outcomes were not shown to be adversely affected by the presence of total ADAb, in the absence of free ADAb and adequate drug levels. However, patients who subsequently developed free ADAb and subtherapeutic or undetectable drug levels had unfavourable long-term outcomes. The presence of total ADAb does not appear to accurately predict the development of free ADAb. This data supports the use of ELISA techniques which measure free ADAb as well as drug levels. Our study and other similar work, 2 suggests that quantification of drug-ADAb complexes (total ADAb) appears to be less relevant to long-term clinical outcomes and therefore, less informative to clinical decision making. References: 1 Ben-Horin S, Chowers Y. Tailoring anti-TNF therapy in IBD: drug levels and disease activity. Nature Reviews Gastroenterology & Hepatology 2014;11 :243–255. 2 van schouwenburg, et al. Long-term measurement of anti-adalimumab using pH-shift-anti-idiotype antigen binding tests shows predictive value and transient antibody formation. Ann Rheum Dis . 2013;72 :1680–6. Disclosure of Interest: None Declared